Gender Gap in Scientific Publications on COVID-19 in Italy During the First Wave of the Pandemic: An Observational Study - Mazzalai, Elena; Turatto, Federica; De Vito, Corrado (Frontiers in Public Health, 2022)
Background: Worldwide, concerns rise on how COVID-19 pandemic impacted heavily on women, even on those belonging to the scientific community. The Italian scientific production regarding the COVID-19 throughout the first months of the health emergency could help to understand the heft of female researchers in this unique period. Objectives: This study aims to investigate the gender gap in the scientific production on COVID-19 in Italy during the first months of the pandemic. Methods: A systematic search of the literature was conducted and, for each included study, first and last author’s gender, type of study, number of co-authors, type of affiliation, journal’s Impact Factor (IF) and specialization were extracted. Descriptive and univariate analyses were performed. Results: 22.2% of the articles were signed by a woman as first author, 18.1% as last authors. Female authorship was less frequent than male authorship regardless of the type of study, number of co-authors, type of affiliation and field of specialization. Conclusion: This analysis reveal a low prevalence of studies with a female first or last author and suggests that the low share of female authors publishing on COVID-19 during the considered timespan is a transversal issue throughout the Italian medical field.